2014
DOI: 10.1128/mbio.01038-13
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Regulation of the Yersinia pestis Cyclic AMP Receptor Protein Crp and Impact on Virulence

Abstract: The cyclic AMP receptor protein (Crp) is a transcriptional regulator that controls the expression of numerous bacterial genes, usually in response to environmental conditions and particularly by sensing the availability of carbon. In the plague pathogen Yersinia pestis, Crp regulates the expression of multiple virulence factors, including components of the type III secretion system and the plasminogen activator protease Pla. The regulation of Crp itself, however, is distinctly different from that found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 65 publications
2
70
0
1
Order By: Relevance
“…Indeed, Pla is required for the full virulence of Y. pestis during both bubonic and pneumonic plague (Lathem et al, 2007; Sodeinde et al, 1992). Pla activates host fibrinolysis during bubonic plague to enable dissemination from the skin to distal sites (Degen et al, 2007), and during pneumonic plague, Pla is required for the massive outgrowth of bacteria observed in the lower airways and is maximally expressed during the pro-inflammatory phase of disease (Lathem et al, 2007; Lathem et al, 2014). The mechanisms by which Pla contributes to bubonic vs. pneumonic plague may be distinct, however, and the host proteins cleaved by Pla in the lungs to alter inflammation and enhance disease during pneumonic plague are not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Pla is required for the full virulence of Y. pestis during both bubonic and pneumonic plague (Lathem et al, 2007; Sodeinde et al, 1992). Pla activates host fibrinolysis during bubonic plague to enable dissemination from the skin to distal sites (Degen et al, 2007), and during pneumonic plague, Pla is required for the massive outgrowth of bacteria observed in the lower airways and is maximally expressed during the pro-inflammatory phase of disease (Lathem et al, 2007; Lathem et al, 2014). The mechanisms by which Pla contributes to bubonic vs. pneumonic plague may be distinct, however, and the host proteins cleaved by Pla in the lungs to alter inflammation and enhance disease during pneumonic plague are not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that Hfq is required for the production of multiple T3SS effector proteins by Y. pseudotuberculosis (20 (1,18,19,32). Therefore, to eliminate the effects of Pla on the T3SS, we deleted the CDS of pla from the pgm-negative strain of Y. pestis.…”
Section: Hfq Participates In the Regulation Of The Y Pestis T3ssmentioning
confidence: 99%
“…For instance, Hfq and sRNAs participate in the regulation of biofilms produced by uropathogenic E. coli, V. cholerae, and Y. pestis, as well as in the regulation of alpha-toxin synthesis in Staphylococcus aureus (23,(25)(26)(27)(28)(29). Indeed, Hfq and sRNAs have been shown to contribute to the virulence of a number of pathogens, including both Y. pestis and Y. pseudotuberculosis (20,(30)(31)(32).…”
mentioning
confidence: 99%
“…While it is possible that the host response to a high dose of the ⌬pla mutant delivered to the lungs may differ from that of wild-type Y. pestis given at lower doses, our results are consistent with a Pla-dependent cleavage of Prdx6 in vivo at 48 h, while pla is maximally expressed. Indeed, the snapshot of the infection at 48 h allows us to make the best examination and comparison of Pla-dependent processes within the lungs, as this is when pla is upregulated by Y. pestis during pneumonic plague and when the proinflammatory response is fully induced in response to the infection (35,55). While there is a Pla-dependent decrease in extracellular Prdx6 protein levels in the lungs after 48 h, we were unable to detect Prdx6 cleavage products in vivo, as is observed following cleavage of Prdx6 by Pla in vitro.…”
Section: Discussionmentioning
confidence: 99%